Local Governance and Rural Development Practices in Nepal - Kharel, Suman (NUTA Journal, 2019)
Local governance particularly means democratic participation of the stakeholders in local development. In this process, rural development creates productive environment for market-led and environment friendly development that enrich quality of life of the people. The landscapes of local governance and rural development have been changing with new way of understanding. International communities are now realizing the transformative role of local governance and education. Nepalese government also has been facing many challenges while implementing local governance and rural development efforts. In this context, this paper reflectively appraised local governance and rural development practices of Nepal from decentralization theory and capability approach. However, subsequent discussions are presented based on secondary data, information and literatures. My discussions show that government of Nepal implemented local self-governance act-1999 for proper decentralization of power/jurisdiction in grassroots. Even though, since two decades local governance mechanisms are working with less capable staff and without elected bodies. For implementation of new constitution-2015, federal government restructured 753 local governance units. In that situation this paper came up with the argument that government mechanism need to foster institutional capability by mobilizing skilled manpower for implementing devolved 22 power/jurisdictions in local levels.